2016
DOI: 10.1007/s13765-016-0172-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional dissection of myeloid-derived suppressor cells

Abstract: Myeloid-derived suppressor cells (MDSCs) are originated and differentiated population from common hematopoietic progenitor cells. Generally, in the late stage of inflammation, MDSCs differentiation and expansion are promoted to suppress the over-activated immune system so that the immune system can maintain the homeostasis. Recently, it has been revealed that MDSCs accumulate in cancer patients and tumor-bearing experimental animals, and these tumor-derived MDSCs suppress anti-tumor immunity by secreting immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Indeed, the immune cell profile in the BM of OB-Runx2 À/À mice showed a significant increase in immunosuppressive MDSCs, Tregs, and Bregs and a decrease in the number of CD3 þ and CD8 þ T cells. Furthermore, the production of cytotoxins was attenuated, and the expression of T-cell exhaustion markers (PD-1 and TIM-3) was upregulated in CD8 þ T cells from the BM of these mice, further suggesting that OB-Runx2 deficiency creates an immune suppressive microenvironment that favors multiple myeloma dissemination (36,43). Multiple myeloma challenge in OB-Runx2 þ/þ and OB-Runx2 À/À mice confirmed these findings and demonstrated that this immunesuppressive BM microenvironment induced by OB-Runx2 deficiency indeed promotes multiple myeloma bone-homing and tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the immune cell profile in the BM of OB-Runx2 À/À mice showed a significant increase in immunosuppressive MDSCs, Tregs, and Bregs and a decrease in the number of CD3 þ and CD8 þ T cells. Furthermore, the production of cytotoxins was attenuated, and the expression of T-cell exhaustion markers (PD-1 and TIM-3) was upregulated in CD8 þ T cells from the BM of these mice, further suggesting that OB-Runx2 deficiency creates an immune suppressive microenvironment that favors multiple myeloma dissemination (36,43). Multiple myeloma challenge in OB-Runx2 þ/þ and OB-Runx2 À/À mice confirmed these findings and demonstrated that this immunesuppressive BM microenvironment induced by OB-Runx2 deficiency indeed promotes multiple myeloma bone-homing and tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Similar cells were later on reported in various other forms of cancer. Tumor produced vascular endothelial growth factor (VEGF) acts as a chemo attractant for these cells ( 3 , 5 ). Transplanted tumors in mice also induced the production of these cells ( 6 , 7 ) with similar activity of inhibiting antigen dependent T cell activation ( 8 ).…”
Section: Ontogeny and Phenotypic Characterization Of Mdscs: Appearancmentioning
confidence: 99%
“…Most of our knowledge till date is mostly based on tumor models and cancer patients, but consistent interest of different fields in this area focused the relevance of these cells in non-cancer situations where over activated immune system need to be suppressed and wherein MDSCs proved as a boon for maintaining homeostasis in immune regulation ( 3 ). Due to the phenotypic and functional heterogeneity, the exact mechanism how MDSCs develop, accumulate, and function is still unveiling.…”
Section: Introductionmentioning
confidence: 99%
“…Another subset further characterized in human MDSC is the immature MDSC (also known “early‐stage MDSC” [eMDSC]), which is defined as Lin—(including CD3, CD14, CD15, CD19, CD56) HLA‐DR‐ CD33+ (Figure ) (Bronte et al, ; Damuzzo et al, ; Mandruzzato et al, ). Recently, human F‐MDSCs (Fibrocytic MDSCs) are characterized as a novel MDSC subset with fibrocytic phenotypes and immunosuppressive functions are defined as CD11b low CD11c low CD33 + IL‐4Ra + (Gunaydin, Kesikli, & Guc, ; Han & Yang, ; Mazza et al, ).…”
Section: Introductionmentioning
confidence: 99%